Analisis Yuridis Penerapan Konsep Asas Lex Specialis Sytematis Dalam Tindak Pidana Perpajakan - Jannah, Miftahul (Indonesian Journal Publisher, 2024)
The sustainability of a country's development heavily relies on its revenue streams, with taxation being a crucial pillar in generating state income. However, corruption within the taxation sector poses a significant threat, leading to substantial losses in state revenue and hindering efforts to enhance societal welfare. This research endeavors to address this challenge by examining the application of criminal law in combating corruption within the taxation sector. Furthermore, the research identifies the role of the Lex Specialis Systematis in delineating taxation crimes from broader financial crimes. While taxation crimes are confined to the realm of tax-related finances, corruption transcends this boundary, impacting broader state finances. This study advocates for a comprehensive legal approach that integrates both tax law and anti-corruption legislation. It underscores the necessity of applying the principles of Lex Systematic Specialist to taxation laws, ensuring that taxpayers are held accountable within the framework of tax regulations. Simultaneously, it emphasizes the applicability of anti-corruption laws, governed by the principles of Lex Specialis, to combat corruption within the taxation sector effectively.In conclusion, this research highlights the imperative of a harmonized legal framework that synergizes tax law and anti-corruption measures. By bridging the gap between these legal domains, the state can enhance its capacity to combat corruption within the taxation sector, safeguard state revenues, and foster sustainable development for the benefit of society at large.